Analisis Swot Pada UKM Toko Kaca & Aluminium di Jalan Raya Pagang Siteba Kota Padang - Nurul Huda Nabillah; Nazla Aulia Azzahara; Sarah Kemala Oktaviani; Era Fikhamsuna Purba; Bunga Aisya; Pasha Dwi Novita; Anisa Firma; Ashifa Putri Mahira (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research was conducted to analyze the internal and external environmental issues of the “Singgalang Baru” glass and aluminium shop in the form of SWOT analysis. This research uses descriptive qualitative research methodology, and the data collection is in three main techniques, such as; 1) direct observation, 2) in-depth interviews with shop owners, and 3) documentation in the form of photos. This research used SWOT matrix analysis, the strategies obtained are SO, WO, ST, and WT strategies. The obstacles faced by “Singgalang Baru” include: 1) the lack of the business management, where human resources are still lacking especially technician staff, 2) challenges in optimizing marketing (ex. showcase) products with strategic locations, 3) the use of technology in marketing and buying and selling systems, and 4) lack of innovation in making products based by glass and aluminum materials. After conducting the analysis, the researchers concluded that the main effort to increase the competitiveness of the “Singgalang Baru” glass and aluminium shop was carried out with the SO strategy, where the strategy focuses on using strengths to take advantage of existing opportunities.